Kinetic Desorption and Sorption of U(VI) during Reactive Transport in a Contaminated Hanford Sediment - Qafoku, Nikolla P; Zachara, John M; Liu, Chongxuan; Gassman, Paul L; Qafoku, Odeta S; Smith, Steven C (Environmental science & technology, 2005)
Column experiments were conducted to investigate U(VI) desorption and sorption kinetics in a sand-textured, U(VI)-contaminated (22.7 μmol kg-1) capillary fringe sediment from the U.S. Department of Energy (DOE) Hanford site. Saturated column experiments were performed under mildly alkaline conditions representative of the Hanford site where uranyl−carbonate and calcium−uranyl−carbonate complexes dominate aqueous speciation. A U(VI)-free solution was used to study contaminant U(VI) desorption in columns where different flow rates were applied. Sorbed, contaminant U(VI) was partially labile (11.8%), and extended leaching times and water volumes were required for complete desorption of the labile fraction. Uranium(VI) sorption was studied after the desorption of labile, contaminant U(VI) using different U(VI) concentrations in the leaching solution. Strong kinetic effects were observed for both U(VI) sorption and desorption, with half-life ranging from 8.5 to 48.5 h for sorption and from 39.3 to 150 h for desorption. Although U(VI) is semi-mobile in mildly alkaline, subsurface environments, we observed substantial U(VI) adsorption, significant retardation during transport, and atypical breakthrough curves with extended tailing. A distributed rate model was applied to describe the effluent data and to allow comparisons between the desorption rate of contaminant U(VI) with the rate of short-term U(VI) sorption. Desorption was the slower process. We speculate that the kinetic behavior results from transport or chemical phenomena within the phyllosilicate-dominated fine fraction present in the sediment. Our results suggest that U(VI) release and transport in the vadose zone and aquifer system from which the sediment was obtained are kinetically controlled.